Rewording the World: Poststructuralism, Deconstruction and the 'Real' in Environmental Education - Noel Gough; Leigh Price (Environmental Association of Southern Africa, 2004)
In this paper we question the desirability of the near-schism between (on the one hand) environmental philosophers, advocates and educators who appear to be antagonistic to, and/or dismissive of, poststructuralism and deconstruction and (on the other hand) those that find these philosophies and methodologies generative in their inquiries. We examine the claims of writers who assert that poststructuralism and deconstruction are anti-realist positions and suggest alternative ways of thinking about these matters that might enable environmental educators who currently take opposing positions to work in more commensurable ways.